A "Push-Pull" rearrangement while routing for a driverless delivery vehicle. Issue 1 (1st January 2019) - Tetouani, Samir; Chouar, Abdelssamad; Lmariouh, Jamal; Soulhi, Aziz; Elalami, Jamila
Abstract: A home delivery logistics network is able to deliver goods to the home in reusable smart-boxes transported by Driverless Delivery Vehicles (DDV). Since the delivery vehicle does not have a human driver, in this case, how to deliver, pick up and rearrange smart-boxes into the Driverless Delivery Vehicles efficiently during routing? In this paper, we combine the results of works on the high density storage system and the results of works which solve sub-optimally the (n 2 -1)-puzzle, for to propose a new " Rearrangement While Routing " strategy for a Driverless Delivery Vehicle based on " snake-line arrangement " and " Pull–Push Rearrangement ". Furthermore, we compare our strategy with three other strategies arrangement based on Manhattan Distance, Number of moves and a Hybrid arrangement combined both Manhattan Distance and Number of moves. The results show that the proposed " Pull–Push Rearrangement " is most efficient in terms number of moves and displacements.